Synthesis of phytochelatins in vetiver grass upon lead exposure in the presence of phosphorus - Andra, Syam S.; Datta, Rupali K.; Sarkar, Dibyendu; Mullens, Conor P.; Sahi, Shivendra Vikram; Bach, Stephan B H; Makris, Konstantinos C. (My University, 2010)
In a hydroponic setting, we investigated the possible role of phytochelatins (metal-binding peptides) in the lead (Pb) tolerance of vetiver grass (Vetiveria zizanioides L.). Pb was added to the nutrient medium at concentrations ranging from 0 to 1,200 mg L -1. Furthermore, we simulated the effect of soil phosphorus (P) on potentially plant available Pb by culturing vetiver grass in P-rich nutrient media. After 7 days of exposure to Pb, we evaluated the Pb uptake by vetiver grass. Results indicate that vetiver can accumulate Pb up to 3,000 mg kg -1 dry weight in roots with no toxicity. Formation of lead phosphate inhibited Pb uptake by vetiver, suggesting the need for an environmentally safe chelating agent in conjunction with phytoremediation to clean up soils contaminated with lead-based paint. Unambiguous characterization of phytochelatins (PC n) was possible using high pressure liquid chromatography coupled with electrospray ionization mass spectrometry (LC-ESMS). Vetiver shows qualitative and quantitative differences in PC n synthesis between root and shoot. In root tissue from vetiver exposed to 1,200 mg Pb L -1, phytochelatins ranged from PC 1 to PC 3. Collision-induced dissociation of the parent ion allowed confirmation of each PC n based on the amino acid sequence. Possible Pb-PC 1 and Pb 2-PC 1 complexes were reported in vetiver root at the highest Pb concentration. The data from these experiments show that the most probable mechanism for Pb detoxification in vetiver is by synthesizing PC n and forming Pb-PC n complexes.
Keywords: Hydroponics; Lead-based paint; Liquid chromatography; Mass spectrometry; Phytoremediation; Vetiver; Phytochelatins